Media dan Teknologi Pembelajaran PPKn dalam Memenuhi Tujuan dan Fungsi Pendidikan Kewarganegaraan - Dhea Kristiani Hutasoit; Lia Wildah Hasanah; Mutiara Lubis; Reyny Puspita Lubis; Sintya Rindi Utami; Nur Raudah Putri; Marisa Zahrani Nasution (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
The digitalization of learning media in the world of education is increasingly visible. The aim of this research is to analyze the strengthening of Citizenship Education learning through learning media. This research uses a qualitative research method with a literature study approach. Citizenship education is an important thing to study in order to understand how citizens carry out their roles, rights and responsibilities for the country. There are various studies that have proven the effectiveness of several learning media for PPKn, including Powtoon, Anchor Podcast, Android Applications, and Roleplay.